Some schemical studies on the processing of cocoa with special emphasisi on flavour constituents - Abeygunasekera, D.D. (My University, 1989)
The thesis deals with some aspects of processing of Theobroma Cocoa. In this study, plant material was collected from Wariapola estate, Matale, which has a mixed plantation of forestero and criollo varieties - typical of cocoa plantations in Sri Lanka. The selected aspects of processing were studied for samples taken both in the major and minor seasons - variations in the parameters measured in this study for these two seasons (which can be considered to be two possible extreames of sample material from any particular estate) was very slight...